Social comparison and interaction anxiety as it correlates to social media usage among students: basis for a proposed Psychological Program - Baylon, Elijah Joaquin P.; Cruz, Jane Frances Renee, Lopez, Kate Andrea P.; Novora, Ma. Josefa A.; Salazar, Charlotte R. and Vilda, Keith Kimberly A. 4 0 16; 5 (2023)
u
Undergraduate Thesis: Bachelor of Science in Psychology, Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2